2020
DOI: 10.1111/andr.12806
|View full text |Cite
|
Sign up to set email alerts
|

Association between prostate‐specific antigen and serum testosterone: A systematic review and meta‐analysis

Abstract: Background Serum testosterone assays are an important tool in the clinical evaluation of a number of endocrine disorders including male hypogonadism. However, serum testosterone has a limited role in real clinical use due to its inaccuracy. We aimed to assess the association between prostate‐specific antigen (PSA) and testosterone as well as the effects of various types of testosterone replacement therapy (TRT) for PSA level. Methods Two electronic databases were screened: PubMed (1966 through December 2018) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(67 reference statements)
1
2
0
Order By: Relevance
“…The level of PSA was higher in males of old age group of prostate cancer as compared to normal case as indicated in Figure 3. Furthermore, the results of our study were confirmed by the (Kim et al, 2020) that explained higher level of PSA was seen in prostate patients as (P<0.05). Higher level of PSA can result in prostate gland cells tumors and complications during hypogonadisom as (P<0.05).…”
Section: Calculationssupporting
confidence: 85%
“…The level of PSA was higher in males of old age group of prostate cancer as compared to normal case as indicated in Figure 3. Furthermore, the results of our study were confirmed by the (Kim et al, 2020) that explained higher level of PSA was seen in prostate patients as (P<0.05). Higher level of PSA can result in prostate gland cells tumors and complications during hypogonadisom as (P<0.05).…”
Section: Calculationssupporting
confidence: 85%
“…As a result, we retrospectively analyzed 31 charts of men treated with hCG monotherapy for hypogonadal symptoms and evaluated changes in hormones, symptoms, and side effects. We found that hCG monotherapy improved hypogonadal symptoms without the undesirable side effects of hCG (gynecomastia, headache, and gastrointestinal complaints) or exogenous testosterone (polycythemia or thromboembolic events) [ 6 , 7 ]. While we did not observe a significant increase in testosterone level, previous literature shows that hCG was able to increase patient T levels; therefore, the lack of increase in T levels could be attributed to the low dose of hCG in our study [ 8 - 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The androgen receptor (AR) target gene, known as prostate-specific antigen (PSA), has been recently reported as a possible marker of AR expression due to the correlation between PSA expression and the transcription of additional AR genes [2,3]. Our previous meta-analysis suggested that normal-range PSA levels could serve as a surrogate indicator of serum testosterone, and another prior study comprising a cohort of apparently healthy men showed that normal-range PSA levels, possibly reflective of androgen activity, could predict subclinical and clinical cardiovascular diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%